2018
DOI: 10.1002/cphc.201800823
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Proton and Charge Transfer of Pyrene‐based trans‐Stilbene Salicylic Acids Applied to Detection of Aggregated Proteins

Abstract: Two analogues to the fluorescent amyloid probe 2,5-bis(4'-hydroxy-3'-carboxy-styryl)benzene (X-34) were synthesized based on the trans-stilbene pyrene scaffold (Py1SA and Py2SA). The compounds show strikingly different emission spectra when bound to preformed Aβ1-42 fibrils. This remarkable emission difference is retained when bound to amyloid fibrils of four distinct proteins, suggesting a common binding configuration for each molecule. Density functional theory calculations show that Py1SA is twisted, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Previously, we showed that bovine insulin could form two types of amyloids under different solvent conditions:toxic fibrils and less toxic filaments, which formed in the presence of a reducing reagent 12 . Certain amyloid-specific luminescent-conjugated oligothiophenes (LCOs) such as pFTAA, and benzothiadiazole (BTD) derivatives 13 , could discriminate between the two different insulin amyloids 14,15,16 . We also demonstrate that human insulin can form toxic amyloid from intact insulin ((i)-amyloid), and less toxic amyloid formed by insulin treated with reducing reagents ((r)-amyloid); we then used these human insulin amyloids as a model of insulin balls.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that bovine insulin could form two types of amyloids under different solvent conditions:toxic fibrils and less toxic filaments, which formed in the presence of a reducing reagent 12 . Certain amyloid-specific luminescent-conjugated oligothiophenes (LCOs) such as pFTAA, and benzothiadiazole (BTD) derivatives 13 , could discriminate between the two different insulin amyloids 14,15,16 . We also demonstrate that human insulin can form toxic amyloid from intact insulin ((i)-amyloid), and less toxic amyloid formed by insulin treated with reducing reagents ((r)-amyloid); we then used these human insulin amyloids as a model of insulin balls.…”
Section: Introductionmentioning
confidence: 99%
“…S2 ), supporting that the droplets are filled with amyloids 35 . It is plausible that PK could bind to the insulin amyloid in the droplet since pyrene and its derivatives were shown to bind to various amyloids with hydrophobic interactions 36 , 37 .…”
Section: Resultsmentioning
confidence: 99%
“…We are using TTR as a research platform to understand small-molecule recognition and binding specificity in our work to facilitate these efforts. , While the structure of TTR was originally solved in 1978 and hundreds of structures of TTR variants and TTR complexes are present in the protein database (PDB), the binding modes of TTR ligands are still a matter of intense research: Recently, a quinoline-derived D–A–D-type fluorescent probe was utilized by Sun et al to study its binding to wild-type TTR, while previous work by some of us has identified a pyrene-based trans-stilbene ligand with a salicylic acid moiety (Py1SA) as an amyloid fibril probe for several different amyloid proteins. Py1SA is an amyloid fluorophore containing a combination of a salicylic acid trans-stilbene conjugated with a pyrene . Its design was based on the pan-amyloid Congo red analogue X-34 and the pyrene moiety from its extensive fluorescence lifetime.…”
Section: Introductionmentioning
confidence: 99%